Effects of Dietary Fatty Acids on Insulin Resistance, Tissue Lipid Profile and Adipose Tissue Cellularity in Sprague-Dawley Rat - Woldemariam, Tekeleselassie Ayalew (2009)
Insulin resistance describes a dysfunctional state of glucose metabolism which often occurs in advance of any metabolic diseases in human population. Dietary fatty acids are closely linked to insulin resistance as they are known to modulate fatty acid and glucose metabolism in mammals. In this study, fatty acids from butter, soybean and menhaden oil were separately incorporated into rat chow diet to assess the differential effect of dietary fatty acids on the various indicators and risk factors of insulin resistance. These include glucose clearance functions, plasma insulin, body composition, tissue and plasma fatty acid profiles, blood lipids, adipose cellularity and leptin level. A total of 40 male Sprague-Dawley rats of 9 weeks age, randomly allocated to four treatment groups of ten animals each, were employed in this study. The treatment groups consisted of rats fed with chow diet (CD), rats fed chow diet fortified with 10% w/w butter (BCD), rats fed chow diet added with 6.67 % w/w menhaden oil and 3.33% w/w soybean oil (MCD), and rats fed chow diet added with 3.33 % w/w menhaden oil and 6.67 % w/w soybean oil (SCD). The rats were subjected to their respective treatment diets for 22 weeks and body weight was measured weekly. Intraperitoneal glucose tolerance test (IPGTT) and intraperitoneal insulin tolerance test (IPITT) were carried out on day 0, and then later in the 12th and 20th weeks of dietary intervention to assess changes as a result of insulin resistance. Serial plasma insulin levels were also quantified on day 0 and in the 20th week. Upon termination of the trial at the end of the 22nd week, post mortem body composition and inguinal fat cellularity were performed on the rats. Plasma leptin and blood lipids in all treatment groups were measured. Determination of fatty acid profile of selected tissues (plasma, red blood cell membrane, liver and skeletal muscle) were also carried out. Generally, tissue and plasma fatty acid profiles were reflective of the dietary fatty acid composition. Results showed that glucose clearance in all treatment groups was not compromised as a result of dietary intervention. However, the BCD group consistently showed higher blood glucose spike 15 minutes after initial glucose loading, and higher blood glucose readings even after insulin challenge during IPITT compared to the other groups. The glucose clearance capacities of MCD and SCD fed animals remained similar to that of their initial baseline values even after 20 weeks of treatment. Unlike glucose concentration, plasma insulin level was significantly (P<0.05) higher in a majority of time points in the BCD rats compared to the MCD and SCD rats in the 20th week. The corresponding total amount of plasma insulin by time as indicated by the area under the plasma insulin curve, (AUC) for the BCD rats was 456.7±27.7 ng/L min. This was significantly higher (P<0.05) than those of the CD (335.5±38.5 ng/L min), MCD (273.7±37.6 ng/L min) and SCD (265.9±21.7 ng/L min) rats. Area under the curve (AUC) values also showed that all treatment groups, (CD, MCD and SCD) had much higher (P<0.05) plasma insulin values after 20 weeks of treatment, compared to their baseline concentration of 200.3±21.6 ng/L min. Apart from being hyperinsulinaemic, the insulin sensitivity index of BCD rats was found to be significantly (P<0.05) compromised unlike those of the MCD and SCD rats. Risk factors associated with insulin resistance such as excessive body fat accumulation and adipocyte cellularity were altered by dietary fatty acids. Inguinal fat cellularity results showed large and hypertrophied adipocytes in the BCD rats, while adipocytes in the MCD and SCD rats became hyperplastic but significantly smaller (P<0.05) than those of BCD rats. Plasma leptin was elevated significantly (P<0.05) in the BCD rat (3.22±0.32 ng/mL) compared to MCD (2.37±3.2 ng/mL), SCD (2.29±0.35 ng/mL) and CD (2.16±0.11 ng/mL) groups. Blood lipid picture was found to be healthier in the MCD and SCD supplemented groups. These two groups had significantly (P<0.05) lower total cholesterol and triacylglycerol (TAG) contents than the BCDfed rats. This was accompanied by significantly reduced high density lipoprotein cholesterol (HDL-C) in the MCD (0.15±0.05 mmol/L) and SCD (0.19±0.05 mmol/L) rats, compared to a value of 0.34±0.07 mmol/L observed for the BCD rats. Therefore, it was concluded that 10% dietary fat supplementation from menhaden and soybean oil could delay the onset of hyperinsulinaemia, and possibly insulin resistance in the rat model. Furthermore, PUFA was also shown to have an effect on the risk factors and other indicators for insulin resistance such as adipocyte cellularity, blood lipids and leptin.